READING TECHNIQUES TO IMPROVE PUPILS' READING COMPREHENSION (American Journal of Research in Humanities and Social Sciences, 2023)
The article dwells on how to construct effective learning techniques to foster reading skills which have been included in the syllabus of each and every primary and secondary schools.